Observation of an intermediate phase in tungsten doped Sb2Te phase change thin films by temperature dependent measurements of structural, optical, and electronic properties. (25th May 2016) - Guo, S; Huang, T; Xu, L P; Shi, K; Zhang, J Z; Ji, X L; Hu, Z G; Wu, L C; Song, Z T; Chu, J H
Abstract: The optical properties, electronic structure, and microstructure of Sb2 Te (ST) phase change films as functions of temperature and tungsten (W) concentration have been investigated by means of temperature dependent x-ray diffraction (XRD), Raman scattering, and spectroscopic ellipsometry. Based on the variations of the diffraction peaks, phonon modes, and dielectric functions during the temperature elevation process, the intermediate (INT) crystalline state of W doped Sb2 Te (WST) films between amorphous (AM) and hexagonal (HEX) phases can be readily proposed, which is a mixture of crystalline Sb and Te. The anomalous behaviors of dielectric functions and partial spectral weight integral for crystalline films elucidate the existence of INT state. Furthermore, the good agreement between experimental and calculated dielectric functions reveals that the first-principles calculation method can be used to make qualitative analysis in the materials with similar multilayered structures.